Identification of a Novel Lipid Metabolism-Associated Hepatic Gene Family Induced by Estrogen via ERα in Chicken (Gallus gallus) - Li, Hong; Li, Yanmin; Yang, Liyu; Zhang, Dingding; Liu, Ziming; Wang, Yanbin; Han, Ruili; Li, Guoxi; Li, Zhuanjian; Tian, Yadong; Kang, Xiangtao; Liu, Xiaojun (Frontiers in Genetics, 2020)
Liver is the main organ of lipid metabolism in chicken, especially for laying hens. To explore the molecular mechanism of lipid metabolism in chicken, five novel genes discovered in chicken liver tissue were systematically studied. Bioinformatic analysis was used to analyze the gene characteristics. The expression patterns and regulatory molecular mechanism of the five genes were examined. Our results showed that all five novel genes contain a common NADP-binding site that belongs to the NADB-Rossmann superfamily, and the genes were designated NADB-LER1-5. Phylogenetic tree of the NADB-LERs gene family in different species suggested these five genes originated from the same ancestor. Tissue distributions showed that NADB-LER1-4 genes were highly expressed in lipid metabolism organs, including liver, kidney and duodenum, and that the NADB-LER5 gene was highly expressed in liver and kidney. The spatiotemporal expression indicated that the expression levels of NADB-LER1-5 genes in liver tissue were significantly greater in sexually mature hens than that of immature pullets (P-value ≤ 0.05). The expression levels of NADB-LER1-5 were significantly induced by 17β-estradiol in primary cultured chicken embryo hepatocytes (P-value ≤ 0.05), and 17β-estradiol regulated the expression of NADB-LER1-5 mediated by ERα. Individual assays verified that under induction of 17β-estradiol, the five novel genes were significantly upregulated, with subsequent alteration in serum TG, TC and VLDLs in 10-week-old pullets. This study proved NADB-LERs family mainly expressed in liver, kidney and duodenum tissues. 17β-estradiol induces the expression of NADB-LER1-5 genes predominantly mediated via ERα. They are likely involved in lipid metabolism in the liver of chicken.